Animal bones in old graves: a zooarchaeological and contextual study on faunal remains and new dated evidence for the ritual re-use of old cemetery sites in Southern and Western Finland - Auli Bläuer (SPRINGER HEIDELBERG, 2022)
Animal remains from twelve Iron Age (ca. 500 BC-1200/1300AD) sites from Southern and Western Finland, showing a mixture of finds and features typical of both settlement sites and cemeteries, were investigated using a zooarchaeological, taphonomic and contextual approach. Rarefaction analysis of the species richness and anatomical distribution indicates that the samples included both general domestic waste type and species and element-selective deposits of cattle and horse skulls, mandibles and limb bones. According to radiocarbon dating results, there seems to be a gap between the dates of burials and those of other ritual activities, indicating that the context of such deposits is a disused cemetery. The faunal deposits could represent remembrance rituals or relate to votive offerings intended to ensure healthy or productive livestock, a practice described in later ethnographic sources. These deposits seem to be in use within a large geographical area over a long period, and some aspects of this belief system may even have survived into the Christianisation of society in the historical period.